FAKTOR DETERMINAN MEMBANGUN MINAT BELI ONLINE - Haning Kusuma; Muhamad Trihudiyatmanto (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract. This study aims to determine the factors that influence online buying interest in the Sociolla marketplace. The variables studied were trust, ease of use, electronic word of mouth, and sales promotion. The background of this research is the decline in buying interest on the Sociolla website from July 2019 - September 2020. This study uses primary data generated from distributing questionnaires. By using the Purpose Sampling technique, a sample of 108 respondents was obtained. The method used in this research is quantitative research. Then the answers of the respondents were analyzed using a structural equation model that was operated with the AMOS program. The results of this study indicate that the variables of trust, ease of use, electronic word of mouth, and sales promotion have a positive effect on purchase intention. The limitation in this study is that the respondents were taken from users of the Sociolla marketplace who made purchases in the last 6 months, so that the results cannot be generalized to all online marketplaces throughout Indonesia. Suggestions from the authors for further research can develop a model by looking for other variables that can influence online buying interest.